1995
DOI: 10.1139/z95-009
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle of a sea louse, Caligus elongatus von Nordmann, 1832 (Copepoda, Siphonostomatoida, Caligidae)

Abstract: Caligus elongatus, known as a sea louse, is a very important pathogen of sea-farmed Atlantic salmon (Salmo salar). The life cycle of C. elongatus was examined under laboratory conditions. The observations were made at 10 °C, with ambient photoperiod. Small Arctic char (Salvelinus alpinus) kept in full-salinity seawater were used as experimental host fish. They were infected individually by offspring of several C. elongatus females. The hosts were killed at consecutive time periods after infection and developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 7 publications
3
35
1
Order By: Relevance
“…The most extensively studied species is C. elongatus, a species with a broad range of hosts, which has been reported from more than 80 different species (Kabata 1979). The lifecycle of C. elongatus is similar to L. salmonis with the exception that C. elongatus lacks the pre-adult stages (Piaseki & McKinnon 1995). Kabata (1979) listed Atlantic halibut as one of the hosts for C. curtus but, so far, this species has not been recorded on farmed halibut.…”
mentioning
confidence: 99%
“…The most extensively studied species is C. elongatus, a species with a broad range of hosts, which has been reported from more than 80 different species (Kabata 1979). The lifecycle of C. elongatus is similar to L. salmonis with the exception that C. elongatus lacks the pre-adult stages (Piaseki & McKinnon 1995). Kabata (1979) listed Atlantic halibut as one of the hosts for C. curtus but, so far, this species has not been recorded on farmed halibut.…”
mentioning
confidence: 99%
“…Initially, Caligus elongatus was the only major pest caligid to the Atlantic salmon farming industry in E Canada (Piasecki & MacKinnon 1995), and Hogans & Trudeau (1989) reported C. elongatus at prevalences up to 100%, compared to Lepeophtheirus salmonis at a maximum of only 8%. In recent years, however, L. salmonis has become the primary pest species, just as it is in the Atlantic salmon farming industry in both Europe (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…= 0.835 to 0.948), indicating a marked differential longevity of males and females on wild fish. Piasecki & MacKinnon (1995) found that male C. elongatus (infesting experimental char Salvelinus alpinus) die soon after copulation. None of the independents here analyzed by stepwise regression (Table 2) correlated significantly with variation in the proportion of female C. elongatus amongst individual fish; but if male postcopulatory death is typical of C. elongatus on wild salmon, then this alone could explain the extreme female bias.…”
Section: Demography Of Lepeophtheirus Salmonis Andmentioning
confidence: 98%
See 1 more Smart Citation
“…Males die after copulation. Females overwinter [Piasecki and MacKinnon, 1995]. Two mitochondrial genotypes have been described for Caligus elongatus Nordman in Norway [Øines and Heuch, 2007].…”
Section: Caligus Elongatus Nordman 1832mentioning
confidence: 99%